Structures and Interactions of Transmembrane Targets in Native Nanodiscs. (December 2019) - Overduin, Michael; Esmaili, Mansoore
Transmembrane proteins function within a continuous layer of biologically relevant lipid molecules that stabilizes their structures and modulates their activities. Structures and interactions of biological membrane–protein complexes or "memteins" can now be elucidated using native nanodiscs made by poly(styrene co-maleic anhydride) derivatives. These linear polymers contain a series of hydrophobic and polar subunits that gently fragment membranes into water-soluble discs with diameters of 5–50 nm known as styrene maleic acid lipid particles (SMALPs). High-resolution structures of memteins that include endogenous lipid ligands and posttranslational modifications can be resolved without resorting to synthetic detergents or artificial lipids. The resulting ex situ structures better recapitulate the in vivo situation and can be visualized by methods including cryo-electron microscopy (cryoEM), electron paramagnetic resonance (EPR), mass spectrometry (MS), nuclear magnetic resonance (NMR) spectroscopy, small angle x-ray scattering (SAXS), and x-ray diffraction (XRD). Recent progress including 3D structures of biological bilayers illustrates how polymers and native nanodiscs expose previously inaccessible membrane assemblies at atomic resolution and suggest ways in which the SMALP system could be exploited for drug discovery.